The relation between SARS-CoV-2 cases in Bahrain and meteorological parameters: 27 months of data - Alnaser, Waheeb E.; Alnaser, Naser W.; Almarabheh, Amer J.; Al-Ansari, Ahmed M.; Al-Aali, Hala H.; Ghanem, Amjad Z. (Frontiers in Built Environment, 2022)
Background: There has been a belief in and strong thought about the existence of a relationship between meteorological parameters and the spread of SARS-CoV-2. Many studies have been conducted but with a short period of investigation, i.e., not more than 4 months. Therefore, the relation between 27 months of SARS-CoV-2 recorded data and meteorological parameters is reported. The aim of this study is to use this vast data to examine whether average temperature, average wind speed, and absolute humidity are clearly correlated with the number of infected SARS-CoV-2 cases in Bahrain or not, which may be applicable to countries that have similar topography. Method: The official recorded data of SARS-CoV-2 cases in Bahrain from the first day that SARS-CoV-2 cases were detected (February 24, 2020) until May 18, 2022, along with 4 meteorological parameters (temperature, wind speed, relative humidity, and absolute humidity) were used. The data were analyzed using SPSS where a p-value less than 0.05 was considered as statistically significant. Result: There is a negative significant correlation between new daily cases of SARS-CoV-2 and temperature, T, and absolute humidity, AH, (r = −0.290, −0.317; p < 0.001, respectively). The results also show a positive significant correlation between daily cases of SARS-CoV-2 and wind speed (V) (r = −0.110; p = 0.002). No correlation was found between daily cases of SARS-CoV-2 and relative humidity (r = −0.028; p = 0.429). An empirical relation is reported, allowing the estimation of SARS-CoV-2 cases in Bahrain as a function of three weather parameters: T, AH, and V.